Act of Announcing the Ideological and Political Declaration Camp of the National Unity in the Face of Selected Titles of the National and Conservative Press - Bończak, Jędrzej (Vade Nobiscum, tom XX/2019: Studia z historii politycznej i wojskowej, 2019)
The foundation of Camp of National Unity (CNU) on February 21st of 1937 had significant influence on shaping of the political landscape in Poland after the death of marshall Józef Piłsudski. The Ideological-Political Declaration of the new organization announced on Polish Radio by its leader – col. Adam Koc ended the period of internal transformations among the government and was aimed at strengthening its influence on the society. The creation of CNU was initiated by Commander-in-Chief, Marshall Edward Śmigły-Rydz and was intended to consolidate the nation around the army and its superior to improve the defense of the country. At the same time, it expressed Śmigły-Rydz’s political ambitions who therefore tried to solidify his social status as an influential co-founder of Polish politics together with the President Ignacy Mościcki and foreign minister Józef Beck. The government started the extensive informational and propaganda campaign to promote its actions. The transformations related to creation of CNU and Śmigły-Rydz’s group activities impacted the opposition parties as well and forced it to take stand against this national initiative, since they posed a threat on the parties’ impact on society. With no other means of participation in political discussion, opposition groups expressed their attitudes toward CNU in the articles published in their own press. The main assumption of this text was to present the reaction of right-wing and centreright- wing circles as the most “affected” by the actions of the sympathizers of Śmigły-Rydz. The attempt to reconstruct an accurate image of these relations was based on articles published by representatives of these circles in their press organs in the period from the date of announcing the Ideological-Political Declaration to the beginning of March 1937. The selected cross-section of time from which the source material comes allows for to follow closely the moods of circles vitally interested in transformation the political scene. At the same time, its tightening became necessary due to the gradual emergence of new issues, which were in fact the result of the existing conditions, but less and less related to the act of the Idea-Political Declaration itself. The evaluated materials come from digital resources of National Library of Poland, as well as catalogues of The Józef Piłsudski Regional and Municipal Public Library in Łódź and Library of University of Łódź. The introduction and the chapter about overall political situation was written based on available publications, especially the book „Silni – Zwarci – Gotowi: myśl polityczna Obozu Zjednoczenia Narodowego” written by Jacek Majchrowski and „Piłsudczycy bez Piłsudskiego. Powstanie Obozu Zjednoczenia Narodowego w 1937 r.” by Tadeusz Jędruszczak.